Severe lung disease characterized by lymphocytic bronchiolitis, alveolar ductitis, and emphysema (BADE) in industrial machine‐manufacturing workers. Issue 11 (28th August 2019) - Cummings, Kristin J.; Stanton, Marcia L.; Nett, Randall J.; Segal, Leopoldo N.; Kreiss, Kathleen; Abraham, Jerrold L.; Colby, Thomas V.; Franko, Angela D.; Green, Francis H.Y.; Sanyal, Soma; Tallaksen, Robert J.; Wendland, Douglas; et al.
Abstract: Background: A cluster of severe lung disease occurred at a manufacturing facility making industrial machines. We aimed to describe disease features and workplace exposures. Methods: Clinical, functional, radiologic, and histopathologic features were characterized. Airborne concentrations of thoracic aerosol, metalworking fluid, endotoxin, metals, and volatile organic compounds were measured. Facility airflow was assessed using tracer gas. Process fluids were examined using culture, polymerase chain reaction, and 16S ribosomal RNA sequencing. Results: Five previously healthy male never‐smokers, ages 27 to 50, developed chest symptoms from 1995 to 2012 while working in the facility's production areas. Patients had an insidious onset of cough, wheeze, and exertional dyspnea; airflow obstruction (mean FEV1 = 44% predicted) and reduced diffusing capacity (mean = 53% predicted); and radiologic centrilobular emphysema. Lung tissue demonstrated a unique pattern of bronchiolitis and alveolar ductitis with B‐cell follicles lacking germinal centers, and significant emphysema for never‐smokers. All had chronic dyspnea, three had a progressive functional decline, and one underwent lung transplantation. Patients reported no unusual nonoccupational exposures. No cases were identified among nonproduction workers or in the community. Endotoxin concentrations were elevated in two air samples; otherwise, exposures were below occupational limits. Air flowed from areas where machining occurred to other production areas. Metalworking fluid primarily grew Pseudomonas pseudoalcaligenes and lacked mycobacterial DNA, but 16S analysis revealed more complex bacterial communities. Conclusion: This cluster indicates a previously unrecognized occupational lung disease of yet uncertain etiology that should be considered in manufacturing workers (particularly never‐smokers) with airflow obstruction and centrilobular emphysema. Investigation of additional cases in other settings could clarify the cause and guide prevention.